Lieve Donnellan, Valentino Nizzo, Gert-Jan Burgers (eds) Contexts of Early Colonization - Fitzjohn, Matthew (Journal of Greek Archaeology, 2017)
One of the most significant phenomena of early Greek history was the growth in the number of settlements around the Mediterranean that have been identified as Greek poleis. The subject of early Greek colonisation, which includes the processes of migration, the foundation of settlements, and the relationships between migrants and indigenous populations, has undergone fundamental reappraisal in the past 35 years.